Local Anesthesia in Dental Patients with Professional Pathology - Abdusalomova M.U.; Istamova V.I; Isaev U.I. (Scholars Digest Publishing, 2023)
Pain is a unique psycho-physiological state of a person that arises as a result of exposure to his or her body of extremely powerful external or internal irritants. Pain is a protective mechanism; it informs about the disease, warns of a disorder in the activity of both individual organs and the entire body. When minimal external irritants are present, there is a change in the overall tone of the nervous system towards either inhibition or excitation; accordingly, special reactions to the surrounding environment also change. Dental diseases rank second in terms of visits. Most diseases and their treatments are accompanied by varying degrees of pain reaction and its consequences. Therefore, adequate pain relief during dental interventions is one of the important and constant components of the therapeutic work of a dentist. Pain relief during dental interventions remains one of the topical tasks in dentistry [2].
Keywords: Local anesthetics, side effects, drugs with local anesthetic effect.